Seborrheic dermatitis - pathogenesis, epidemiology and effective treatment - literature review - Piotr Sobkiewicz; Maciej Józefiak; Joanna Kania; Krzysztof Kania; Maciej Jędrak; Karolina Niekurzak (Kazimierz Wielki University, 2023)
Introduction: Seborrheic dermatitis (SD) is common inflammatory dermatology disease. It's affect up to 3-8% of the population. SD is characterized by erythema yellowish plaques and different level of itching and scaling. The last two symptoms are important factors that affect the quality of life of patients. This condition is usually a reaction to growth of  Malassezia spp and commonly develop in regions of strong sebaceous glands such as the scalp, facial area, chest, back. Other factors include increased activity of sebaceous glands, immunosuppression, and stress. Aim of the study: A review of current stage of knowledge on the pathophysiology, epidemiology of Seborrheic Dermatitis. Recommended management with newest guidelines of this disease. The impact of the Covid-19 pandemic and the use of masks on the incidence of Seborrheic Dermatitis. Material and methods: This review was based on available data searched in the PubMed and Google Scholar by using key words: Seborrheic dermatitis, pathophysiology, epidemiology, diagnosis, treatment, clinical presentation, scalp, infant.  Conclusion: The Pathogenesis of Seborrheic dermatitis is not fully understood, the exact molecular process needs to be examined. SD is chronic disease with episode of remission and relapse of symptoms. Patients should be informed that ongoing maintenance treatment will be required. Treatment include topical antifungal (ketoconazole, Ciclopirox olamine, zinc pyrithione) and topical anti-inflammatory drugs like mild or mid-strength corticosteroids or calcineurin inhibitors (off-label use). In severe or resistance cases systematic therapy could be necessary. In this situation antifungal drugs (terbinafine, itraconazole) or low dose of isotretinoin are available options. Also new synergic treatments were introduce like cannabinoids or vitamin D which could make therapy more efficiency.